100k views
2 votes
30 points! I don't know where to start here if I'm being honest. Please explain your answer in detail?

30 points! I don't know where to start here if I'm being honest. Please explain your-example-1

1 Answer

5 votes

Answer:

The sum of the first six terms is


32-8+2-0.5+(1)/(8)-(1)/(32)=25.59

Explanation:

Given series is 32-8+2-0.5+...

We may write
{\{32,-8,2,-0.5,...}\}

Let
a_(1)=32,a_(2)=-8,a_(3)=2,a_(4)=-05,...

Common ratio
r=(a_(2))/(a_(1))


r=(-8)/(32)


r=(-1)/(4)


r=(a_(3))/(a_(2))


r=(2)/(-8)


r=(-1)/(4)

Therefore the common ratio is
r=(-1)/(4)

Therefore given sequence is of the form of Geometric sequence

The nth term of the geometric sequence is


a_(n)=ar^(n-1)

First to find the 5th and 6th term

That is substitute n=5 and n=6 ,a=32 and
r=(-1)/(4) in above equation we get


a_(5)=32((-1)/(4))^(5-1)


a_(5)=32((-1)/(4))^(4)


a_(5)=32[((-1)/(4))* ((-1)/(4))* ((-1)/(4))* ((-1)/(4))]


=(1)/(8)

Therefore
a_(5)=(1)/(8)


a_(6)=32((-1)/(4))^(6-1)


a_(6)=32((-1)/(4))^(5)


a_(6)=32[((-1)/(4))* ((-1)/(4))* ((-1)/(4))* ((-1)/(4))* ((-1)/(4))]


=(-1)/(32)

Therefore
a_(6)=-(1)/(32)

Therefore the sum of the first six terms is


32-8+2-0.5+(1)/(8)-(1)/(32)


=25.5+(3)/(32)


=(819)/(32)


=25.59

Therefore the sum of the first six terms is


32-8+2-0.5+(1)/(8)-(1)/(32)=25.59

User TNA
by
5.2k points